Roadwork - Sutton, Sally (Candlewick Press, 2008)
There are many big machines and busy people involved in building a road, and this picture book, with its rambunctious rhymes and noisy fun, follows them every step of the way, from clearing a pathway to rolling the tar to sweeping up at the end.